PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP KINERJA MANAJEMEN KEUANGAN UMK: (Studi Pelaku Usaha Mikro Bidang Kuliner di Kota Surabaya) - Ute Ch. Nasution; Akbar Nugroho (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
MSMEs are one of the main actors in the development of a country's economic sector. The resilience of MSMEs is proven by the ability to withstand the existing financial crises. However, the development of MSMEs is hampered by several internal and external problems, with one of the main problems being the low awareness of business actors about financial management. Good financial management is influenced by several factors, where the focus in this study is the financial literacy factor and financial attitude owned by MSE’s (Micro and Small Enterprises). Good financial literacy will make business people able to utilize knowledge in the field of finance in making the right decisions in improving their business performance. While a good financial attitude can improve an individual's behavior towards the money he has. So the author is interested in compiling a study entitled